Evatuation of aqueus extracts for six plants in controling on the tow spotted spider Mite Tetranychus urticae Koch under laboratory conditions (Submission and Review of Research -Biological Sciences Series, 2025)
Laboratorical are carried out to ditermine the effects of aqueous extracts for six plant species Aloe barbadensis, Ammi visnaga, Nigella sativa, Ocimum basilicum and Rosamarinus officinalis on the eggs and adults of Tetranychus urticae and on femal fecundity by treating Leaf disks. Mortality ratio calculated by Abbott equation analysed statisticaly and the resultes showed high differences within the studied plants species. The resultes of the study confirmed that some plant extracts have a good efficacy on the adults of T.urticae when treated with the extracts of both the N.sativa, A.visnaga 100% and 98.82% respectively without significant difference between them. The mortality percentage was 95% when treated with F. vulgare in the end of experiment. The T.urticae eggs hatchability decreased to 0% when treated with the extract of N.sativa and to 11.67% for both of A.visnaga and Abamectine with no significant fifference between them. The hatchability was 95% with the A. barbadensis plants extracts effected fecundity treated females, that the more effective were of N. sativa, Abamectin and A. visnaga with no significant difference between them. The hatchability was 95% With the A. barbadensis plants extracts effected fecundity treated females, that the more effective were of N. sativa, Abamectin and A. visnaga with no significant difference between them. Followed by R. officinalis and F. vulgare 12.86%. In conclusion N.sativa and A.visgnaga extracts showed better effectiveness than other studied plants extracts.